2018
DOI: 10.1108/ijge-07-2017-0041
|View full text |Cite
|
Sign up to set email alerts
|

The impact of bank financing and internal financing sources on women’s motivation for e-entrepreneurship

Abstract: Purpose The purpose of this paper is to examine the impact of bank financing and internal financing sources on women’s motivation for e-entrepreneurship. Design/methodology/approach Female owners of e-businesses in India were surveyed regarding their perceptions of bank financing, internal financing sources and their motivations for e-entrepreneurship. Findings The findings of this study show that bank financing and internal financing sources positively impact women’s motivation for e-entrepreneurship in I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…These results are in line with those reported by Inmyxai and Takahashi (2012), Tachibana (2014), Kyophilavong et al (2016), Leitch et al (2018) and Basco (2019) regarding what shapes the decision to become an entrepreneur in the socialist transition economy of the Lao PDR. It is recognized that financing accumulation is a necessity for women entrepreneurs to use for start-up capital (Koropp et al , 2014; Thiele and Wendt, 2017; Kwapisz and Hechavarría, 2018; Mand et al , 2018; Kim, 2018; Edelman et al , 2018). This sharpens Derera et al (2014), Eldomiaty et al (2018) and Salerno’s (2019) perspective that well-accumulated financing may increase the optimal stock of capital and also preclude a sizable amount of available choices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with those reported by Inmyxai and Takahashi (2012), Tachibana (2014), Kyophilavong et al (2016), Leitch et al (2018) and Basco (2019) regarding what shapes the decision to become an entrepreneur in the socialist transition economy of the Lao PDR. It is recognized that financing accumulation is a necessity for women entrepreneurs to use for start-up capital (Koropp et al , 2014; Thiele and Wendt, 2017; Kwapisz and Hechavarría, 2018; Mand et al , 2018; Kim, 2018; Edelman et al , 2018). This sharpens Derera et al (2014), Eldomiaty et al (2018) and Salerno’s (2019) perspective that well-accumulated financing may increase the optimal stock of capital and also preclude a sizable amount of available choices.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated that, in order to finance the attractive investment involved in working capital, small family firms must appear to be strong in start-up capital (e.g. Mand et al , 2018; Roomi et al , 2018; Shiri et al , 2018; Edelman et al , 2018; Pimentel et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The two do not necessarily have a causal connection. The results of this study can only be applied to those who are comparable to the (Swain & Wallentin, 2009)participants (Mand et al, 2018)). A social entrepreneurship intervention called "Pahal Initiative" with the aid of a social entrepreneur, helped the women in the family launch a food delivery service.…”
Section: Review Of Papersmentioning
confidence: 91%
“…This is evident in many Asian cultural contexts that are more patriarchal than western cultures. For example, previous research by Mand, Atri, Gill, and Amiraslany () suggested Indian women entrepreneurs have been negatively impacted by the country's conservative culture. Moreover, Simmons, Wiklund, Levie, Bradley, and Sunny () in a study of 8,171 entrepreneurs from 35 countries using GEM data found women entrepreneurs are more deterred by failure compared to men, which affects their ability to reenter the marketplace.…”
Section: Literature Reviewmentioning
confidence: 99%